2018
DOI: 10.1097/mcg.0000000000000917
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk of Mortality Associated With Pancreatic Exocrine Insufficiency in Patients With Chronic Pancreatitis

Abstract: PEI was a significant independent risk factor for mortality in patients with CP. These results support further research into the optimal treatment of PEI to reduce mortality in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
50
0
17

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(67 citation statements)
references
References 45 publications
0
50
0
17
Order By: Relevance
“…While long‐term randomised placebo‐controlled trials are lacking, medium term follow up studies note improved nutritional parameters, weight, symptoms, and quality of life 37,38 . One retrospective study suggested exocrine pancreatic insufficiency was associated with reduced survival in patients with chronic pancreatitis 39 . A number of cohort studies, 22,40,41 a population‐based cohort study, 26 and some small randomised trials 42,43 have assessed the benefit of PERT in patients with pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…While long‐term randomised placebo‐controlled trials are lacking, medium term follow up studies note improved nutritional parameters, weight, symptoms, and quality of life 37,38 . One retrospective study suggested exocrine pancreatic insufficiency was associated with reduced survival in patients with chronic pancreatitis 39 . A number of cohort studies, 22,40,41 a population‐based cohort study, 26 and some small randomised trials 42,43 have assessed the benefit of PERT in patients with pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of exocrine pancreatic insufficiency (EPI) is 60%‐90% in advanced chronic pancreatitis (CP) and 50%‐90% in pancreatic cancer (PC) 1 . Untreated, EPI results in fat and protein malnutrition, muscle wasting, metabolic bone disease, reduced quality of life and even mortality 2 . Based on various clinicopathological parameters, the diagnosis of PC is usually accurate.…”
Section: Chronic Pancreatitis (N = 37 061) Pancreatic Cancer (N mentioning
confidence: 99%
“…This can lead to osteoporosis, poor immunity status, and an increased risk of cardiovascular events. All these complications seriously affect the quality of life of patients with PEI …”
Section: Clinical Manifestationsmentioning
confidence: 99%